Pioneers of the botanical exploration of South America – Early 19th Century Jean-Théodore Decourtilz (1796–1855) - Ossenbach, Carlos; Jenny, Rudolf (Lankesteriana: International Journal on Orchidology, 2017)
Jean-Théodore Descourtilz (1796-1855) was a well-known ornithologist who produced beautiful illustrated books on Brazilian birds. Less-known is an unpublished manuscript with water-colours of Brazilian orchids, which was adquired by the wealthy French Baron Delessert, who send it on loan to John Lindley. Lindley described dozens of new orchid species based on Descourtilz’ illustrations and used several of them as models for his beautiful publication Sertum Orchidaceum.